2014
DOI: 10.1590/0104-07072014001740013
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with obesity and overweight in school-aged children

Abstract: ABSTRACT:To assess the factors associated with excess weight (overweight/obese) in school children enrolled in the public education network in Divinópolis, Minas Gerais, Brazil. Cross-sectional study with 1187 children between 6 and 14 years of age from municipal schools in Divinópolis, Minas Gerais. The prevalence of obesity and overweight was calculated based on the parameters of the World Health Organization, using the WHO Anthro-Plus Program. Logistic regression was used to identify the variables associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
6

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
10
0
6
Order By: Relevance
“…The authors studied 941 children from public (state and municipal) and private schools, aged 10-14 years, in the city of Campo Grande (MS) and found that 23.1% of the children were overweight 20. Souza, when studying 1187 students from public elementary schools in Divinópolis (MG) aged 6-14 years, found 24.4% of the children with obesity and overweight, with 23.5% in girls and 22.6% in boys 21.…”
Section: Discussionmentioning
confidence: 99%
“…The authors studied 941 children from public (state and municipal) and private schools, aged 10-14 years, in the city of Campo Grande (MS) and found that 23.1% of the children were overweight 20. Souza, when studying 1187 students from public elementary schools in Divinópolis (MG) aged 6-14 years, found 24.4% of the children with obesity and overweight, with 23.5% in girls and 22.6% in boys 21.…”
Section: Discussionmentioning
confidence: 99%
“…20 The prevalence of overweight in this study was lower than that found in a study conducted with schoolchildren enrolled in the municipal public school system in Divinópolis-MG, where 24.4% of the students were overweight. 21 The prevalence of overweight and obesity in this investigation it was also lower than the general one among adolescents in Brazil in which 23.1% were overweight. 22 The frequency of overweight identified in this study was similar to that found in Ouro Preto (MG) where 19.8% of the adolescents were overweight.…”
Section: Methods Introductionmentioning
confidence: 40%
“…Recomenda-se pelo menos 150 minutos de atividade física semanal de nível moderado ou 75 minutos de nível vigoroso no sentido de melhorar o estado de saúde (SOUZA et al, 2014). A atividade física é uma forma de lazer e de restaurar a saúde dos efeitos nocivos que o estresse do cotidiano proporciona.…”
Section: Introductionunclassified